Pitfalls in the diagnosis of carnitine palmitoyltransferase 1 deficiency - Grünert, Sarah; Berger, Urs; Hörster, Friederike; Schwarz, Kathrin; Thimm, Eva; Spiekerkötter, Ute; Haas, Dorothea; Schumann, Anke (The journal of pediatric endocrinology and metabolism, 2025)
Objectives Carnitine palmitoyltransferase 1A (CPT1A) deficiency is an ultra-rare autosomal recessive disorder of the carnitine cycle caused by biallelic pathogenic variants in the CPT1A gene. It mainly presents with a hepatic phenotype and is a target disease of newborn screening programs worldwide. Disease-specific and diagnostic abnormalities of CPT1A deficiency comprise elevated concentrations of free carnitine as well as an elevated metabolite ratio [C0/(C16 + C18)] in blood, but the ideal sample material has been a matter of debate. Methods We present biochemical data of five CPT1A deficient patients, of whom four were diagnosed by newborn screening from dried blood spots. Results Our cases demonstrate that acylcarnitine profiles and especially concentrations of free carnitine can be normal in plasma in infants with CPT1AD at confirmation diagnosis after screening and during follow-up. Even the [C0/(C16 + C18)] ratio yielded normal results in some cases. Conclusions Our data show, that dried blood is the preferred sample material for the diagnosis of CPT1A deficiency as it is superior to serum/plasma with respect to diagnostic sensitivity and reliability in quantification of the ratio [C0/(C16 + C18)]. CPT1A deficiency can be missed, if the analysis is only performed in serum or plasma, and confirmatory diagnostics in serum or plasma after screening can be false negative.
Online veröffentlicht am 29. September 2025
Gesehen am 27.01.2026